Some New Results Concerning the Fourier Coefficient in Function Space Type of Lorentz?Morrey with Many groups of Variables (London Journal of Research In Science: Natural and Formal, 2023)
In this paper I provide more general notions for generalized Fourier series and convergence of Fourier series in Lorentz-Morrey space with many groups of variables. This conceptual framework is very important in other areas in mathematics (such as ordinary and partial differential equations) and physics (such as quantum mechanics and electrodynamics). As applications I study of summability of Fourier coefficients for functions from some Lorentz-Morrey type spaces with many groups of variables.
Keywords: m? set; Hamming m? codes; steganography; m? protocol F5.; the space type of Lorentz?Morrey; the function space of differentiability function; some properties of these spaces; many groups of variables.